Every Doctor : Healthier Doctors = Healthier Patients - Rowe, Leanne; Kidd, Michael (CRC Press, 2018)
"Every Doctor spoke to me deeply and personally ... as we face the challenges of 21st Century medical practice, I felt cared for, much like I do when visiting my personal family doctor. Every Doctor will speak to you as well."Associate Professor Sandy Buchman, Family Physician Practising in Palliative Care, President-Elect of the Canadian Medical Association "As implicit in the title, the book reaches out to every doctor from recent graduates to the experienced - general practitioner and specialist. The message is universal, timeless and challenging."Emeritus Professor John Murtagh, Department of General Practice, School of Primary Health Care, Faculty of Medicine Nursing and Health Sciences, Monash University, Australia "Michael and Leanne are indeed the best family doctors to author Every Doctor because they have demonstrated in this book how much they understand about us as medical practitioners, as leaders and advocates, and about our journeys and our future. They share precious experience and offer precious advice."Dr Donald Li (Hong Kong, China), President, World Organisation of Family Doctors (WONCA), 2018-2020 "If you ever feel like giving up medicine - and all of us have those sorts of days - then this remarkable, courageous and joyful book is the one for you."Dr Iona Heath CBE, President, Royal College of General Practitioners (2009-2012) 'Every Doctor' is about thriving in medicine at a time of massive advances and changes in global health systems and medical services.The book is a must-read for doctors of all specialties at all stages of their careers wherever they practise in the world, because exemplary care of patients, peers, profession and self is a lifelong journey.--
Introduction. Section 1: Every doctor can improve their physical and mental health to provide patient care of the highest standard. Discovering our 'mighty purpose'. Experiencing joy and beauty in medicine. Taking control of our time. Strengthening our personal resilience. Nurturing strong relationships at home. Trusting our own doctor. Prioritising our wellness and physical health . Dealing with immense stress. Living with loss, grief and serious illness . Seeking help for mental health problems early. Section 2: Every doctor can work with colleagues to create a healthier and happier medical culture. Creating healthier clinical teams. Managing challenging behaviours together. Learning from complaints and clinical errors to change systems of care. Calling out conscious and unconscious biases . Eliminating sexual harassment, discrimination and bullying. Preventing and managing patient-initiated violence. Supporting colleagues to respond to serious mental illness. Looking after our physical environment. Section 3: Every doctor can lead and influence positive changes in their workplaces every day. Medical leadership research. Practical aspects of medical leadership. Contributing to global, national and local medical membership organisations. The why and how of healthy everyday medical leadership.
OCLC-licensed vendor bibliographic record.
Keywords: Attitude of Health Personnel; Health behavior; Clinical competence; Quality of Health Care; Physicians